Analisis Pengaruh Likuiditas, Ukuran Perusahaan dan Risiko Bisnis Terhadap Struktur Modal dengan Profitabilitas Sebagai Variabel Intervening (Studi Pada Perusahaan Sub Sektor Makanan dan Minuman di BEI Periode 2014-2020) - Indri Setyani; Gendro Wiyono; Ratih Kusumawardhani (Ekonomis: Journal of Economics and Business, 2022)
This study aims to examine the effect of liquidity, firm size and business risk on capital structure with profitability as an intervening variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2014-2020 period. The population in this study are all food and beverage sub-sector companies that have been and are still listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling and obtained a sample of 9 companies. The data analysis technique used classical assumption test, multiple linear regression and sobel test. The results of this study indicate that liquidity has a positive and significant effect on profitability, while firm size and business risk have no effect on profitability. Liquidity has a negative and significant effect on capital structure, firm size has a positive effect on capital structure, business risk and profitability have no effect on capital structure. Profitability cannot mediate liquidity, firm size and business risk on capital structure.